Storge stability studies on powdered dried banaba leaves (Lagerstroemia Speciosa (L.) Pers.) - Valencia, Julian Jacinto Ignacio; Galvez, Flor Crisanta F. (1995.)
The effects of different blanching time (0.3 and 6 min) and drying temperature (40, 60 and 80°C) on storage stability and sorption isotherm properties of dried powdered banaba leaves used for the production of tea were studied. Results showed that banaba leaves that where blanched for 6 min and dried at 80°C were most stable and can be stored in polyethylene bags for three months without any significant change in their physical and microbiological properties. The water activity ranged from 0.36 to 0.47. The sorption isotherms obtained were asymptotic to the x-axis indicating that the products were relatively stable and did not readily absorb moisture.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Banaba leaves